Entanglement in fermionic systems at a quantum phase transition - Johannesson, Henrik; Larsson, Daniel (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We consider recent results on the use of the single-site entanglement measure for identifying and characterizing a quantum phase transition in systems of interacting fermions. We discuss the extension of these results to fermionic models where the single-site entanglement may fail to signal a quantum phase transition, with particular attention given to the one-dimensional extended UV Hubbard model.